Bid-Ask Bounce and Spreads in Foreign Exchange Futures Market - DING, David K. (Institutional Knowledge at Singapore Management University, 1996)
This paper examines the intraday bid-ask bounce in Deutschemark and Japanese yen futures prices. The intraday Markovian bid-ask bounce process, which leads to a desirable equilibrium condition of reaching a bid or an ask transaction type with equal chances, is identified. A second-order Markov chain transition matrix model is used to derive a generalized estimator of bid-ask spreads in the foreign exchange futures market. It incorporates the conditional probabilities of a subsequent transaction being the same type as the current transaction's (d) and that of the next transaction being the same as the current type but different from the previous type (a). The specification is {-Cov(?Pt,?Pt+1)/[(1-d)(-a)]}1/2. The empirical results show that the average implied bid-ask spread is about $10, which is less than one tick's value of $12.50. It is also found that spreads are higher at the beginning and end of the trading day than the rest of the day, reflecting the uncertainty due to information flows and overnight inventory carrying costs, respectively.